Wisata Virtual: Keterlibatan Masyarakat Bali Aga dalam Promosi Pariwisata Virtual di Masa Pandemi Covid-19 di Bali Utara - Dini Andiani, Nyoman; Arismayanti, Ni Ketut; Anwar Sani, Fitria Earlike; Wiarti, Luh Yusni (Jurnal Kajian Bali (Journal of Bali Studies), 2022)
Five Bali Aga (Old Balinese) tourist villages in Banjar District, North Bali, collaborated to promote their tourism potential through virtual tours two times during 2021 by bringing up different topics each time. This study analyses the process and the community involvement during implementation of virtual tour and also themes that were provided for the virtual tours. In collecting data, this qualitative study involved a literature review, participatory observation, and interviews. Data were analysed using marketing theory and community-based tourism theory. The analysis shows that Bali Aga tourist villages were very active in preparing attractions and conducting the virtual tours. This article contributes to our understanding that virtual tour as a new form of marketing communication in promoting tourist destination virtually. Moreover, virtual tours are not only for tourism promotion but are also useful for helping the community in maintaining their spirit to manage tourist attractions during the pandemic.